Incremental value of carotid elasticity modulus using shear wave elastography for identifying coronary artery disease in patients without carotid plaque. Issue 6 (June 2021) - Wang, Yonghuai; Zhao, Cuiting; Meng, Pingping; Yu, Yao; Li, Guangyuan; Kong, Fanxin; Mu, Lixin; Yang, Jun; Ma, Chunyan
Abstract : Background: Shear wave elastography (SWE) directly quantifies the local arterial wall stiffness by calculating the elastic modulus. However, whether carotid wall elastic modulus can predict obstructive coronary artery disease (CAD) is not well known. We aimed to investigate the value of carotid wall elastic modulus measured using SWE in identifying obstructive CAD. Materials and methods: We prospectively enrolled 61 patients without carotid plaque referred for clinically indicated coronary angiography. Twenty-seven (44.3%) patients were diagnosed with obstructive CAD (≥50% coronary stenosis). The elastic modulus of common carotid artery was quantified using SWE. Ankle--brachial index (ABI) and echocardiographic global cardiac calcium score (GCCS) were measured. Results: Patients with obstructive CAD had significantly higher elastic modulus than those without obstructive CAD. The maximum elastic modulus (EMmax) was independently associated with obstructive CAD after adjusting for the Framingham risk score, ABI, and GCCS. EMmax had the highest area under the curve (AUC) to identify obstructive CAD (AUC 0.70; P = 0.003). In the nested models, the model based on the Framingham risk score and ABI ( χ 2  = 3.74) improved by adding GCCS ( χ 2  = 9.95) and further improved by adding EMmax (χ 2  = 15.86). Adding EMmax to the combined ABI and GCCS model increased integrated discrimination index from 0.10 to 0.19. Conclusion: Carotid wall elastic modulus measured using SWE is a useful predictor of obstructive CAD in patients without carotid plaque. We demonstrated the incremental and independent value of carotid wall elastic modulus in identifying obstructive CAD compared with clinical risk factors and other imaging predictors, including ABI and GCCS. Video abstract: Please see the video, in Supplemental Digital Content 1, http://links.lww.com/HJH/B551 for more insights from the authors. Abstract : Supplemental Digital Content is available in the text